INTERPRETATION OF MYTHS IN THE FILM THE STORY OF THE JAVA LAND OF MERAPI - Nur Izzah Islamy; Muhammad Irfan Riyadi (QAULAN: Journal of Islamic Communication, 2024)
One type of mass media that captivates viewers both with the content and meaning of what they see is film. The theoretical significance of the story of Merapi Island in Java, as well as its use. The purpose of the study of the words "sigh", "object", and "interpretant" in the film is the focus of this investigation. By applying the model of semiotic analysis proposed by Charles Sanders Pierce, the problem of how meaning arises from a sign when the sign is used by people when communicating. The relationship between signs, objects, and interpretations was drawn by Pierce. This research uses a qualitative descriptive approach, systematic data analysis from the collection of facts or a set of numerical values, and enriched with documentation in the form of screenshots from several episodes of the film The Story of the Land of Java Merapi. To examine the film The Story of the Land of Java Merapi and its depiction of the myth that Mount Merapi is home to supernatural beings whose existence is still widely believed to exist, the film The Story of the Land of Java Merapi has 6 episodes in its story and each episode in the film The Story of the Land of Java Merapi has several mythical meanings. The phenomenon of Merapi as a very important local genius, the mythological tradition of the nations of the world describes the existence of a region that is the origin of the development of life and heaven civilization or the place of origin that was then abandoned when suddenly heaven turned into hell. After seeing the Story of the Land of Java Merapi, we hope you don't take everything for granted; instead, we encourage you to think critically about the film.